From welfare to workfare : the unintended consequences of liberal reform, 1945-1965 - Mittelstadt, Jennifer, 1970- (Gender & American culture., 2005)
This book locates the roots of the 1996 welfare reform many decades in the past, arguing that women, work, and welfare were intertwined concerns of the liberal welfare state beginning just after World War II. It examines the reform of Aid to Dependent Children (ADC) and reconstructs the ideology, implementation, and consequences of rehabilitation.